A comparative evaluation of patient satisfaction outcomes in an interprofessional student-run free clinic. Issue 5 (28th August 2015) - Lawrence, David; Bryant, Tara K.; Nobel, Tamar B.; Dolansky, Mary A.; Singh, Mamta K.
Abstract: As the evidence supporting the value of well-coordinated healthcare teams continues to grow, so to do the calls from medical educators and policy makers for the development of meaningful interprofessional educational experiences for health professions students. The student-run clinic has emerged as a unique venue for such experiential interprofessional learning experiences, with over 100 such clinics now in operation across North America. As the number and variety of these clinics rises, it has become increasingly important to understand the quality of care which they deliver. Here, patient satisfaction data from an interprofessional student-run free clinic are described, and these results are quantitatively compared to similar data obtained from a non-interprofessional, non-student-run clinic in a post-experience only, non-equivalent groups design. Student-run free clinic patients reported high levels of satisfaction with the patient care team and the facility quality, and lower levels of satisfaction with waiting times. When compared to the non-student-run clinic, there was no significant difference in the high levels of patient satisfaction with the patient care teams between the clinics. Student-run free clinic patients did, however, report significantly lower levels of satisfaction with the accessibility of care and with the perceived privacy of protected health information. Overall, this report provides evidence that an interprofessional student-run free clinic is capable of performing at the level of an experienced free clinic across many domains of patient satisfaction, while also identifying notable areas for improvement within the domains of clinic accessibility and the perception of the privacy of protected health information.